Waterfall pattern using Omron CP1E PLC, Fuzzy Logic Method, and PLC-IoT approach - Supramono, Supramono (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
Programmable Logic Controller (PLC) used in data processing is OMRON Corp's CP1E type. In this research, a prototype was produced using a solenoid valve amounting to 24 which will be used as output for sequential water based on timer and presser given on parameters. Five experiments are basic patterns: chessboard triangle, zebra cross, off shift, and on shift. The experiment used fuzzy logic parameters to obtain accuracy in the waterfall; the timer is on the ladder diagram to provide the value of the combination of falling water that varies on each pattern. The accuracy value in the range 0-1 on one experiment is off-shifted. At the value of 0.206 bar presser, the water accuracy level is 0.811. At the 0.41 bar presser level, the accuracy level is 0.532; the conclusion produced by the presser is very influential on the water accuracy level at the waterfall. This research applies a PLC approach to the Internet of Things (IoT) for flexibility control and monitoring needs.